Pendampingan pembuatan hand sanitizer berbasis kearifan lokal (ekstrak tangkai bunga cengkeh) - Sundari Sundari; Dharmawaty M. Taher; Nurhasanah Nurhasanah; Said Hasan; Abdu Mas'ud (Universitas Hamzanwadi, 2020)
Efforts to prevent viral infection are a shared responsibility of all Indonesian citizens, including academics. Prevention starts from keeping a distance, wearing a mask, and washing hands. Another alternative to washing hands is to use a hand sanitizer. This community service activity program aims to educate and assist the community in preventing infection with the Covid-19 virus based on local culture through assisting students in making hand sanitizers made from local products, namely clove flower stem extract, and distributing them to the community. The methods used in this activity are production, product distribution, and education (lectures). The team will distribute the product to the Khairun University campus area and six schools in Ternate city. This community service program's result is 300 bottles of clove flower stalk extract and distributed to the public. In general, the community's response to the hand sanitizer product from clove flower stalk extract is that the public is enthusiastic and has good comments on this hand sanitizer product.